Protective effects of a glucocorticoid on downregulation of pulmonary beta 2-adrenergic receptors in vivo. - J C Mak; M Nishikawa; H Shirasaki; K Miyayasu; P J Barnes (The Journal of Clinical Investigation, 1995)
We investigated the in vivo effects of a glucocorticoid on beta-agonist-induced downregulation of beta 1- and beta 2-adrenergic receptors (determined by [125I]iodocyanopindolol binding), mRNA expression (assessed by Northern blotting), and gene transcription (using nuclear run-on assays) in rat lung. Dexamethasone (Dex) (0.2 mg/kg/d, days 1-8) increased beta 1- and beta 2-receptor numbers by 70 and 69% above control, respectively, but did not change their mRNA expression. Isoproterenol (Iso) (0.96 mg/kg/d, days 2-8) decreased beta 1- and beta 2-receptor numbers by 48 and 51%, respectively, and also reduced mRNA expression by 69 and 57%, respectively. The combination of Dex and Iso resulted in no net change in beta 2-receptor number and its mRNA expression, although there was a significant reduction in beta 1-receptor number and mRNA expression. The mapping of beta 1- and beta 2-receptors by receptor autoradiography confirmed these findings over alveoli, epithelium, endothelium, and airway and vascular smooth muscle. We also measured the activation of the transcription factor, cyclic AMP response element binding protein (CREB) using an electrophoretic mobility shift assay. CREB-like DNA-binding activity was decreased after Iso treatment but this decrease was prevented after treatment with Dex. Nuclear run-on assays revealed that the transcription rate of the beta 1-receptor gene did not alter after Dex treatment, but was reduced after Iso treatment. The transcription rate of the beta 2-receptor gene was increased after Dex treatment by approximately twofold, but there was no change after Iso treatment. We conclude that glucocorticoids can prevent homologous downregulation of beta 2-receptor number and mRNA expression at the transcriptional level without affecting beta 1-receptors and that the transcription factor CREB may be involved in this phenomenon. Such an effect may have clinical implications for preventing the development of tolerance to beta 2-agonists in asthmatic patients treated with beta-agonist bronchodilators. Images